2012
DOI: 10.1073/pnas.1208098109
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for functional cooperation between tandem helicase cassettes in Brr2-mediated remodeling of the spliceosome

Abstract: Assembly of a spliceosome, catalyzing precursor-messenger RNA splicing, involves multiple RNA-protein remodeling steps, driven by eight conserved DEXD/H-box RNA helicases. The 250-kDa Brr2 enzyme, which is essential for U4/U6 di-small nuclear ribonucleoprotein disruption during spliceosome catalytic activation and for spliceosome disassembly, is the only member of this group that is permanently associated with the spliceosome, thus requiring its faithful regulation. At the same time, Brr2 represents a unique s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
208
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 93 publications
(219 citation statements)
references
References 26 publications
10
208
0
1
Order By: Relevance
“…Our observation that the isolated ILS dissociates completely in the presence of any rNTP was therefore very surprising in that it indicated that the ATP-specific Brr2 helicase/ ATPase is not required for the ILS disassembly. The recently determined X-ray crystal structure of Brr2 reveals a configuration of amino acid side chains at the nucleotide-binding pocket that exclusively allows binding of ATP (Santos et al 2012). It can thus be ruled out that Brr2 loses its ATP specificity in the context of the spliceosome.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation that the isolated ILS dissociates completely in the presence of any rNTP was therefore very surprising in that it indicated that the ATP-specific Brr2 helicase/ ATPase is not required for the ILS disassembly. The recently determined X-ray crystal structure of Brr2 reveals a configuration of amino acid side chains at the nucleotide-binding pocket that exclusively allows binding of ATP (Santos et al 2012). It can thus be ruled out that Brr2 loses its ATP specificity in the context of the spliceosome.…”
Section: Discussionmentioning
confidence: 99%
“…(D) Interactions involving the E890 residue of human Brr2 (equivalent to E909 in yeast Brr2) in a crystal structure with ADP bound at the NC (PDB ID 4F93). 51 Dashed lines, hydrogen bonds or salt bridges. The rotation symbol indicates the orientation relative to (C).…”
Section: Brr2 Exhibits a Unique Structurementioning
confidence: 99%
“…2A,B). 41,52 Only the N-terminal helicase cassette (NC) is active in nucleotide hydrolysis and RNA unwinding, 51 and the enzymatic activity of the NC alone is required for splicing in vivo. 27 The C-terminal cassette (CC) is still able to bind ATP, 51 but it contains noncanonical residues in the ATP binding and hydrolysis motifs, which abrogate the ATPase activity.…”
Section: Brr2 Exhibits a Unique Structurementioning
confidence: 99%
See 2 more Smart Citations